Review of Australian Scirtes Illiger, Ora Clark and Exochomoscirtes Pic Coleoptera: Scirtidae) including descriptions of new species, new groups and a multi-gene molecular phylogeny of Australian and non-Australian species - Watts, Chris H.s.; Cooper, Steven J.b.; Saint, Kathleen M. (Zootaxa, 2017)
The phylogenetic relationships of 26 Australian species of Scirtes Illiger, Ora Clark and Exochomoscirtes Pic (Scirtidae) were investigated using adult morphology, particularly male and female genitalia, larval morphology and molecular data from the mitochondrial cytochrome c oxidase subunit I (COI) gene and the nuclear genes elongation factor 1-alpha (EF1- a) and topoisomerase I (TOP1). Four species of Scirtes and one of Ora from Europe, Southeast Asia and Japan were included. The genus Scirtes is shown to be paraphyletic with respect to the genera Ora and Exochomoscirtes. Australian Scirtes were shown to belong to four species groups: Scirtes elegans group (Yoshitomi 2009); S. helmsi group (Watts 2004); S. japonicus group (Nyholm 2002); and S. haemisphaericus group (Yoshitomi 2005). The prehensor and bursal sclerite of 15 species are illustrated as well as habitus illustrations of S. zwicki sp. nov. and S. albamaculatus Watts. Three new species from Australia are described: Scirtes lynnae, S. zwicki and S. serratus spp. nov. Scirtes nehouensis Ruta & Yoshitomi 2010 is synonymised with S. emmaae Watts 2004. Scirtes pygmaeus Watts, 2004 is synonymised with S. pinjarraensis Watts, 2006. Scirtes rutai nom. nov. is proposed as a replacement name for S. beccus Ruta, Kiałka & Yoshitomi, 2014 from Sabah as it is preoccupied by S. beccus Watts, 2004 from Australia.